Dermal Patch with Integrated Flexible Heater for on Demand Drug Delivery. Issue 1 (26th October 2015) - Bagherifard, Sara; Tamayol, Ali; Mostafalu, Pooria; Akbari, Mohsen; Comotto, Mattia; Annabi, Nasim; Ghaderi, Masoumeh; Sonkusale, Sameer; Dokmeci, Mehmet R.; Khademhosseini, Ali
Abstract : Topical administration of drugs and growth factors in a controlled fashion can improve the healing process during skin disorders and chronic wounds. To achieve this goal, a dermal patch is engineered that utilizes thermoresponsive drug microcarriers encapsulated within a hydrogel layer attached to a flexible heater with integrated electronic heater control circuitry. The engineered patch conformally covers the wound area and enables controlled drug delivery by electronically adjusting the temperature of the hydrogel layer. The drugs are encapsulated inside microparticles in order to control their release rates. These monodisperse thermoresponsive microparticles containing active molecules are fabricated using a microfluidic device. The system is used to release two different active molecules with molecular weights similar to drugs and growth factors and their release profiles are characterized. This platform is a key step towards engineering smart and closed loop systems for topical applications. Abstract : A wearable drug delivery system based on a hydrogel sheet containing thermoresponsive drug carriers interfaced with a flexible heater is engineered for topical applications. The platform maintains a conformal contact with skin and enables on demand and tunable drug delivery by controlling the hydrogel temperature. The release rates of various molecules with different sizes are studied. The system paves the way toward engineering smart wound dressings.